A rare mutation in the EPG5 gene causes Vici syndrome - Demiral, Emine; Sen, Askin; Esener, Zeynep; Ceylaner, Serdar; Tekedereli, Ibrahim (Lippincott Williams & Wilkins, 2018)
[Abstract Not Available]
Keywords: Sensorineural Hearing-Loss; Corpus-Callosum; Muscle Biopsy; Immunodeficiency; Hypopigmentation; Agenesis